Nitrate has a stronger rhizobacterial-based effect on rice growth and nitrogen use than ammonium in acidic paddy soil - Xiao, Xun; Liu, Zeng Tai; Shen, Ren Fang; Zhao, Xue Qiang (Plant and soil, 2023)
Background and Aims Suitable N source supply is critical to improve plant growth and N uptake, but the importance of nitrate (NO 3 − ) for rice ( Oryza sativa L.) and microbiota is often neglected in acidic paddy soils where ammonium (NH 4 + ) is dominant. This study aimed to explore the differential effects of NH 4 + and NO 3 − on rice growth, fertilizer nitrogen recovery efficiency (FNRE), and rhizosphere bacterial community in acid soil. Methods Two rice varieties, Kasalath (Al-sensitive indica ) and Koshihikari (Al-tolerant japonica ), were exposed to different N sources with or without lime in an acid soil. Results Liming and NO 3 − application solely improved the growth and FNRE of the Al-sensitive rice, namely, by increasing soil pH and alleviating Al toxicity. Compared with liming and rice variety, N source had a more pronounced influence on rhizobacterial community composition. Of the two sources, NO 3 − had a stronger effect on the rhizobacterial community than NH 4 + . Remarkably, rice plants fed with NH 4 + specifically recruited Desulfosporosinus and Desulfitobacterium associated with ferric NH 4 + oxidation in the rhizosphere, whereas those exposed to NO 3 − recruited Alicyclobacillus with NO 3 − -reducing iron oxidation ability. Three keystone taxa were identified in a rhizobacterial co-occurrence network analysis: Alicyclobacillus , which was positively associated with rice growth and FNRE, and Acidobacteriales and WPS-2 , both with negative associations. Conclusion Compared with NH 4 + , NO 3 − enhances the growth and FNRE of Al-sensitive rice and exerts dominant effects on the rhizobacterial community, which indicates the importance of NO 3 − for rice and has instructive implications for N management in acid soil.